TI_GERICHTE 12.2014.40 vom 16. November 2015 , Mandato - responsabilità della banca - moneta - reclamo - stralcio - spese e ripetibili - TI Tribunale d'appello (2015)
Mandato - responsabilità della banca - moneta - reclamo - stralcio - spese e ripetibili